The Impact of Cultural Differences on the Coordination and Control of International Projects - Melchor López, Isidro (My University, 2005)
This study attempts to extend current knowledge of cultural differences in international project management. In particular, the aim of the study is to identify the main cultural differences when coordinating and controlling international projects, how these differences affect on projects and what alternatives can be taken to minimize a negative effect on project performance. The main questions addressed are: 1) what cultural differences arise when coordinating and controlling international projects? 2) how do cultural differences affect coordination and control of international projects? and 3) how could cultural differences be adapted to a company’s working systems to reduce a negative effect on the coordination and control of international projects? The theoretical context of the study mainly includes the Hosfstede’s dimensions and the cultural differences, multicultural teams, project phases, project characteristics and constraints, international project management, the project approach as a management tool, and the coordination and control mechanisms. The research methodology is based on interviews following a qualitative approach as well as a practical comparison among starting projects, on-going projects and totally finished ones. The unit of analysis is the power plant construction project with the different actors involved during its development. Data was collected by interviewing eight international project managers from Wärtsilä, Nestlé, and Pronal who were involved in power plant constructions projects in Mexico and Honduras. This data was analyzed qualitatively by interpreting interviewees’ responses. This study shows that there are culture-bound intangible aspects in the project managers’ way to coordinate and control international projects, which affect the good project performance.
Keywords: cultural differences; coordination; control; international projects; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|